OFF-GAS DESULFURIZATION WITH SODIUM BICARBONATE FOR IRON ORE SINTER PLANTS: INVESTIGATION OF THE INFLUENCE OF THE OFF-GAS TEMPERATURE - Lanzerstorfer, Christof (MATTER: International Journal of Science and Technology, 2017)
For dry off-gas desulfurization by chemisorption in iron ore sinter plants hydrated lime is usually used as reactant. In some other off-gas cleaning applications with a gas temperature above 140°C sodium bicarbonate is used instead of hydrated lime. An advantage of sodium bicarbonate is the higher desulfurization efficiency. Additionally, cooling of the off-gas to a temperature below 100°C to achieve satisfactory desulfurization is not required. In sinter plants the off-gas temperature is often below 140°C. Thus, the thermal decomposition of sodium bicarbonate to sodium carbonate, which increases the specific surface area of the reactant, might be too slow. The aim of this study was to investigate the desulfurization gas with sodium bicarbonate in the typical temperature range of sinter plant off-gas of 110-160°C. The experiments were performed in a small pilot system consisting of an entrained flow reactor and a fabric filter. For the experiments a mixture of sulfur dioxide in air was used. The results showed that the efficiency of the desulfurization was only slightly reduced at the lower temperature of 110°C. However, at lower temperatures it takes longer after start-up of the system to reach stable conditions. At first, the efficiency is lower, but it seems that this is nearly compensated for by reaction in the filter cake, which builds up at the filter. Therefore, sodium bicarbonate is a feasible reactant for the desulfurization of sinter plant off-gas.